Consideration of Severe Coronavirus Disease 2019 As Viral Sepsis and Potential Use of Immune Checkpoint Inhibitors - (:unkn) unknown (My University, 2020)
Taking into consideration the multisystemic clinical and autopsy findings in "severe" coronavirus disease 2019 patients, viral sepsis would be a more accurate term to describe the whole clinical picture. The most significant pathophysiological components of this picture are intense cytokine release, prolonged inflammation, immunosuppression with T cell exhaustion, and the development of organ dysfunctions. Currently, the optimal treatment for severe coronavirus disease 2019 is uncertain. Supportive treatment and immunomodulators have a critical place in the treatment of severe patients until effective antivirals are developed. Interleukin-6 antagonists, one of the immunomodulating agents, appears to be effective in the treatment of cytokine storm, but some patients continue to have severe lymphopenia and immunosuppression. We believe it can be useful as immunomodulator therapy in critical coronavirus disease 2019 patients because of the benefits of immune checkpoint inhibitors in cancer and sepsis patients.
Keywords: sepsis; acute respiratory distress syndrome; coronavirus disease 2019; lymphopenia; NKG2A; programmed cell death protein 1